Alumina-based catalytic ceramic membrane loaded with high-content ferric oxide as well as preparation method and application of alumina-based catalytic ceramic membrane
The preparation of alumina-based catalytic ceramic membrane with high iron oxide loading through ball milling and one-step molding co-sintering method, solving the problems of low catalyst loading and complex preparation process, achieving efficient catalytic performance and the effect of reducing production costs.
Patent Information
- Application Number
- CN202411848559.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The catalyst loading of existing catalytic ceramic membranes is low, resulting in limited catalytic action, complex preparation process and high cost.
Alumina-based catalytic ceramic film loaded with high iron oxide is prepared by ball milling, a binder and a pore-forming agent are added, and a one-step molding co-sintering method is used to prepare an alumina-based catalytic ceramic film supported by high iron oxide.
The catalyst loading is increased to 50%, the preparation process is simplified, the production cost is reduced, and the removal effect of micro-pollutants is significantly improved during the ozone catalytic oxidation process.
Smart Images

Figure CN119751111A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an alumina-based catalytic ceramic membrane loaded with high content of iron oxide and a preparation method and application thereof, belonging to the technical field of inorganic functional ceramic microfiltration membranes and preparation thereof. Background Art
[0002] Endocrine disruptors are a class of substances that can interfere with endocrine function. They have a long half-life and are easily enriched in organisms, posing a serious threat to human health. Membrane technology, as an advanced water treatment technology, is used to remove organic matter from drinking water or sewage. Ceramic membranes have many technical advantages, such as good mechanical properties, anti-pollution, hydrophilicity, acid and alkali resistance, chemical resistance and long life. In water treatment, the molecular weight cutoff of low-pressure driven ceramic membranes is much higher than that of micropollutants, resulting in physical filtration being unable to effectively remove pollutants. In order to overcome this key technical obstacle, it is of great significance to develop functional ceramic membranes with catalytic properties for the removal and degradation of pollutants during the filtration process.
[0003] Ozone oxidation technology can simultaneously utilize the oxidation and decomposition of ozone molecules to produce highly active free radicals, which has a good removal effect on pollutants. And because ozone oxidation technology has no secondary pollution, it is widely used in engineering. Heterogeneous catalysis can promote the decomposition of ozone molecules to produce strong oxidizing OH to improve oxidation efficiency. The catalyst is easy to recycle and occupies a dominant position in ozone catalytic oxidation water treatment.
[0004] At present, the main methods for preparing catalytic ceramic membranes include dip coating, magnetron sputtering, vacuum filtration and hydrothermal / solvothermal synthesis. Although such methods are technically mature, the preparation process is cumbersome, the catalyst can only be loaded on the surface, and the loading amount is often less than 10%. The catalytic effect is limited and it is easy to fall off under the action of hydraulic scouring, which is not conducive to industrial production and application. In addition, the existing ceramic membrane preparation process usually requires multiple high-temperature sintering, which consumes a lot of energy and increases production costs. Therefore, increasing the catalyst loading on the membrane surface and inside and rationally utilizing the sintering process in the ceramic membrane preparation process are the key to improving the catalytic performance of ceramic membranes and reducing preparation costs. Summary of the invention
[0005] In view of the problems that the existing catalytic ceramic membranes have low catalyst loading which limits their catalytic effect, and the preparation process is complex and costly, the present invention provides an alumina-based catalytic ceramic membrane loaded with a high content of iron oxide, and a preparation method and application thereof.
[0006] The technical solution of the present invention:
[0007] One of the purposes of the present invention is to provide a method for preparing an alumina-based catalytic ceramic membrane loaded with a high content of iron oxide, the specific method comprising the following steps:
[0008] (1) ball-milling aluminum oxide, silicon dioxide, iron oxide and water to obtain a powder dispersion;
[0009] (2) adding a binder and a pore-forming agent to the powder dispersion for secondary ball milling, fully mixing, drying, and sieving to obtain a pre-pressed powder;
[0010] (3) placing the pre-pressed powder in a mold and pressing it into shape to obtain a green body;
[0011] (4) Sintering the green body to obtain a catalytic ceramic membrane.
[0012] It is further defined that in (1), the particle size of aluminum oxide is 150 to 1000 nm, the particle size of silicon dioxide is 50 to 500 nm, and the particle size of iron oxide is 30 to 500 nm.
[0013] It is further defined that the molar ratio of aluminum oxide to silicon dioxide in (1) is 1:0.05-3, and the mass of iron oxide is 0.5-50% of the total mass of aluminum oxide and silicon dioxide.
[0014] It is further defined that the ball milling treatment time in (1) is 0.5 to 24 hours.
[0015] It is further defined that the binder in (2) is a mixture of one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, methyl cellulose and polyvinyl alcohol; the added mass of the binder is 0.5 to 50% of the total mass of alumina, silica and silicon oxide.
[0016] It is further defined that (2) the pore-forming agent is a mixture of one or more of corn starch, nanocarbon, yellow dextrin, cyclodextrin, calcium carbonate, and melamine; the added mass of the pore-forming agent is 0.5 to 50% of the total mass of alumina, silica, and silicon oxide.
[0017] It is further defined that the drying temperature in (2) is 40 to 100° C. and the drying time is 0.5 to 12 h.
[0018] It is further defined that the mesh size of the sieving process in (2) is 40 to 400 mesh.
[0019] It is further defined that the molding pressure in (3) is 2 to 60 MPa.
[0020] It is further defined that the green body thickness in (3) is 0.5 to 2.5 mm.
[0021] It is further defined that the sintering conditions in (4) are: raising the temperature from room temperature to 500°C at a rate of 0.5-10°C / min, then raising the temperature to 800°C at a rate of 0.5-15°C / min, keeping the temperature for 0.5-5h, and finally raising the temperature to 900-1600°C at a rate of 0.5-15°C / min, keeping the temperature for 0.5-12h, and then cooling to room temperature at a rate of 2-10°C / min.
[0022] The second object of the present invention is to provide an alumina-based catalytic ceramic membrane loaded with high content of iron oxide prepared by the above method.
[0023] The third object of the present invention is to provide an application of the above-mentioned alumina-based catalytic ceramic membrane loaded with high content of iron oxide, specifically for catalytic ozone oxidation to remove organic pollutants in water.
[0024] Beneficial effects:
[0025] The present invention prepares alumina-based ceramic membranes by adding silicon dioxide to generate a liquid phase to promote sintering during the sintering process, and adds a catalyst α-Fe2O3 to the ceramic powder before sintering, and adopts a one-step molding co-sintering method to prepare a ceramic membrane with catalytic function, which simplifies the preparation process and increases the content of α-Fe2O3 on the surface and inside of the ceramic membrane. In addition, both α-Fe2O3 and Al2O3 are close-packed hexagonal crystals. During the sintering process, Fe 3+ Activate the crystal lattice and promote sintering. And as the amount of α-Fe2O3 added increases, small pores are expelled during the sintering process, the pore walls shrink, large pores are generated, the pore size of the ceramic membrane gradually increases, and the permeation flux of the ceramic membrane is improved. Compared with the prior art, this application also has the following advantages:
[0026] (1) The catalytic ceramic membrane provided by the present invention has a simple preparation process, low raw material price, and a catalyst loading of up to 50%. In the process of ozone catalytic oxidation, the adsorption of α-Fe2O3 on ozone molecules is utilized, and electron transfer occurs between Fe atoms and O atoms, which promotes the decomposition of ozone to produce ·OH and O2 ·- Free radicals, improve the mass transfer process of heterogeneous catalytic ozonation, strengthen the removal effect of low-pressure membrane on micro-pollutants, and the catalytic membrane still maintains good catalytic function under different water quality conditions.
[0027] (2) The catalytic ceramic membrane prepared by the present invention has the characteristics of large pore size and high pure water flux. The removal rate of atrazine in the high flux operation process is more than 80%. Taking the catalytic ceramic membrane with 50% α-Fe2O3 addition as an example, at 380 L·m -2 ·h -1 At a permeate flux of , the removal efficiency of atrazine was 83.1%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD comparison spectra of the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1;
[0029] Figure 2 It is a comparison chart of pure water flux of catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1;
[0030] Figure 3 It is a comparison chart of the removal rate of the pollutant atrazine by the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 when the ozone concentration is 5 mg / L;
[0031] Figure 4 This is the pore size distribution diagram of the catalytic ceramic membrane prepared in Comparative Example 1;
[0032] Figure 5 This is the pore size distribution diagram of the catalytic ceramic membrane prepared in Example 1;
[0033] Figure 6 This is the pore size distribution diagram of the catalytic ceramic membrane prepared in Example 2;
[0034] Figure 7 This is the pore size distribution diagram of the catalytic ceramic membrane prepared in Example 3;
[0035] Figure 8 (a) and (b) are SEM photos of the catalytic ceramic membranes prepared in Comparative Example 1 and Example 3, respectively;
[0036] Fig. 9 This is a thermal gravimetric curve of the catalytic ceramic membrane prepared in Example 3;
[0037] Fig.10 This is a diagram showing the degradation effect of atrazine in water catalyzed by the catalytic ceramic membrane prepared in Example 3 under different ozone concentration conditions;
[0038] Fig.11 This is a graph showing the detection results of superoxide free radicals during catalytic oxidation of the catalytic ceramic membrane prepared in Example 3;
[0039] Fig.12 This is a graph showing the results of detecting hydroxyl radicals during the catalytic oxidation process of the catalytic ceramic membrane prepared in Example 3. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0042] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0043] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.
[0044] Example 1
[0045] The process of preparing the catalytic ceramic membrane in this embodiment is as follows:
[0046] (1) Add 150 ml of water to a ball mill, add 5 g of aluminum oxide, 0.375 g of iron oxide, and 2.5 g of silicon dioxide to the ball mill, and mix thoroughly for 12 h to obtain a uniform powder dispersion;
[0047] (2) adding 0.05 g of polyvinyl alcohol and 2.3 g of corn starch to the dispersion, mixing for 12 h, and then drying the mixed slurry in a vacuum drying oven at 60 ° C and passing through a 200 mesh sieve;
[0048] (3) placing the dry powder in a stainless steel mold and pressing it into a green body at a pressure of 40 MPa;
[0049] (4) The ceramic membrane green body is placed in a tubular furnace, and the heating program is adjusted to increase the temperature to 200°C at a heating rate of 1.0°C / min and keep it at that temperature for 1 hour; then increase the temperature to 800°C at a heating rate of 1.5°C / min and keep it at that temperature for 2 hours; finally, heat to 1200°C at a heating rate of 2°C / min, sinter for 5 hours, and maintain the cooling rate at 2.0°C / min to cool to room temperature to obtain a catalytic ceramic membrane.
[0050] Example 2
[0051] The process of preparing the catalytic ceramic membrane in this embodiment is as follows:
[0052] (1) Add 150 ml of water to a ball mill, add 7.1 g of aluminum oxide, 1.815 g of iron oxide, and 5 g of silicon dioxide to the ball mill, and mix thoroughly for 12 h to obtain a uniform powder dispersion;
[0053] (2) adding 0.05 g of polyvinyl alcohol and 4 g of corn starch to the dispersion, mixing for 24 h, and then drying the mixed slurry in a vacuum drying oven at 60 °C and passing through a 200 mesh sieve;
[0054] (3) placing the dry powder in a stainless steel mold and pressing it into a ceramic membrane green body at a pressure of 50 MPa;
[0055] (4) The ceramic membrane green body is placed in a tubular furnace, and the heating program is adjusted to increase the temperature to 200°C at a heating rate of 3.0°C / min and keep it at this temperature for 0.5 h; then increase the temperature to 800°C at a heating rate of 3.0°C / min and keep it at this temperature for 0.5 h; finally, heat to 1300°C at a heating rate of 3.0°C / min, sinter for 5 h, and maintain the cooling rate at 5.0°C / min to room temperature to obtain a catalytic ceramic membrane.
[0056] Example 3
[0057] (1) Add 150 ml of water to a ball mill, add 3 g of aluminum oxide, 1.75 g of iron oxide, and 1.5 g of silicon dioxide to the ball mill, and mix thoroughly for 12 h to obtain a uniform powder dispersion;
[0058] (2) adding 0.02 g of polyvinyl alcohol and 2 g of corn starch to the dispersion, mixing for 24 h, and then placing the mixed slurry in a vacuum drying oven at 60 ° C to dry it and passing it through a 200 mesh sieve;
[0059] (3) placing the dry powder in a stainless steel mold and pressing it into a ceramic membrane green body at a pressure of 40 MPa;
[0060] (4) The ceramic membrane green body was placed in a tubular furnace, and the heating program was adjusted to heat up to 200°C at a heating rate of 1.5°C / min and keep warm for 0.5h; then the temperature was increased to 800°C at a heating rate of 1.5°C / min and kept warm for 0.5h; finally, the temperature was increased to 1200°C at a heating rate of 1.5°C / min, sintered for 5h, and the cooling rate was maintained at 5.0°C / min to room temperature to obtain a catalytic ceramic membrane, named 50-FeAl.
[0061] Comparative Example 1
[0062] (1) Add 150 ml of water to a ball mill, add 3 g of alumina and 1.5 g of silica to the ball mill, and mix thoroughly for 12 h to obtain a uniform powder dispersion;
[0063] (2) adding 0.02 g of polyvinyl alcohol and 2 g of corn starch to the dispersion, mixing for 24 h, and drying the mixed slurry in a vacuum drying oven at 60 °C, and passing through a 200-mesh sieve;
[0064] (3) placing the dry powder in a stainless steel mold and pressing it into a ceramic membrane green body at a pressure of 40 MPa;
[0065] (4) The ceramic membrane green body was placed in a tubular furnace, and the heating program was adjusted to heat up to 200°C at a heating rate of 1.5°C / min and keep warm for 0.5h; then the temperature was increased to 800°C at a heating rate of 1.5°C / min and kept warm for 0.5h; finally, the temperature was increased to 1200°C at a heating rate of 1.5°C / min, sintered for 5h, and the cooling rate was maintained at 5.0°C / min to room temperature to obtain a catalytic ceramic membrane, named 0-FeAl.
[0066] Effect example
[0067] (1) The XRD comparison spectra of the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 are as follows: Figure 1 As shown by Figure 1 It can be seen that in Examples 1 to 3, characteristic peaks corresponding to α-Fe2O3 (104), (110) and (113) appear at 33.2°, 35.7° and 43.5°, indicating that α-Fe2O3 crystals are successfully added to the ceramic membrane in a single-phase form.
[0068] (2) The pure water flux of the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 was tested using an ultrafiltration cup in a dead-end filtration mode. The results are as follows: Figure 2 As shown by Figure 2 It can be seen that the pure water flux of the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 is 979.26 L·m -2 ·h -1 bar -1 、1105.09L·m -2 ·h -1 bar -1 、1615.97L·m -2 ·h -1 bar -1 and 745.62 L·m -2 ·h -1 bar -1 .
[0069] (3) The catalytic degradation performance of the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 was characterized. The specific test method was as follows: a peristaltic pump was used to deliver saturated O3 water and water in a volume ratio of 4:1 into a dead-end filter device, samples were taken at regular intervals, and excess Na2S2O3 was quickly added to the effluent to terminate the reaction. The test results showed that under the condition of 5 mg / L ozone, the removal rates of atrazine by the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 were 58.63%, 65.3%, 86.2% and 32.1%, respectively.
[0070] (4) The pore size distribution of the catalytic ceramic membranes prepared in Examples 1 to 3 and Comparative Example 1 was tested. The results are as follows: Figures 4 to 7 As shown in the figure, the pore size of the comparative example is 162.4nm. In Example 1, 5% of α-Fe2O3 is added, and the pore size is reduced to 156.8nm. This is mainly due to the addition of α-Fe2O3 blocking the membrane pores and causing the pore size to decrease. In Examples 2 and 3, 15% and 50% of α-Fe2O3 are added respectively, and the pore size increases to 195.5nm and 281.9nm respectively, mainly because Fe2O3 can promote sintering under high temperature conditions and reduce the sintering temperature.
[0071] (5) The microscopic morphology of the catalytic ceramic membranes prepared in Comparative Example 1 and Example 3 was characterized. The results are as follows: Figure 8 As shown in (a) and (b), the pores on the membrane surface of Comparative Example 1 and Example 3 are caused by the combustion of the pore-forming agent. Compared with Comparative Example 1, the surface morphology of the ceramic membrane prepared in Example 3 has no obvious change, and there are a large number of white particles, which are the added α-Fe2O3 catalyst.
[0072] (6) The thermal gravimetric curve of the catalytic ceramic membrane prepared in Example 3 is as follows: Fig. 9 As shown by Fig. 9 It can be seen that in the range of 0-100℃, the mass loss is 3%, which is mainly caused by the volatilization of water molecules in the ceramic membrane. At 300-500℃, the mass loss of the ceramic membrane is 15.1%, which is mainly due to the violent combustion of the pore-forming agent and the rapid decrease in mass. Above 500℃, the mass change is low, the crystal undergoes phase change, and releases heat.
[0073] (7) The catalytic ceramic membrane prepared in Example 3 was tested for its degradation effect on atrazine in ozone-oxidized water under different ozone concentrations. At a water temperature of 25°C, saturated O3 water and 500 μg / L atrazine solution were delivered to a dead-end filtration device using a peristaltic pump at a volume ratio of 20:1, 6:1, 4:1, and 2:1. The catalytic process flux was 380 L·m -2 ·h -1 bar -1 The test results are as follows: Fig.10 As shown by Fig.10 It can be seen that with the increase of ozone concentration, the removal rate of atrazine increases. 5mg / L is the best ozone dosage, and the removal rate of atrazine is 81.7%.
[0074] (8) The superoxide radicals and hydroxyl radicals in the catalytic oxidation process of the catalytic ceramic membranes prepared in Example 3 and Comparative Example 1 were compared. Fig.11 and 12 As shown in the figure, it can be seen that in the catalytic filtration process, Example 3 can effectively catalyze ozone molecules to produce superoxide radicals and hydroxyl radicals. When ozone is added alone or when comparative example 1 is used for experiments, no free radical generation can be detected.
[0075] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing an alumina-based catalytic ceramic membrane loaded with high iron oxide content, characterized in that: include: (1) ball-milling aluminum oxide, silicon dioxide, iron oxide and water to obtain a powder dispersion; (2) adding a binder and a pore-forming agent to the powder dispersion for secondary ball milling, fully mixing, drying, and sieving to obtain a pre-pressed powder; (3) placing the pre-pressed powder in a mold and pressing it into shape to obtain a green body; (4) Sintering the green body to obtain a catalytic ceramic membrane.
2. The preparation method according to claim 1, characterized in that: (1) The particle size of aluminum oxide is 150 to 1000 nm, the particle size of silicon dioxide is 50 to 500 nm, and the particle size of iron oxide is 30 to 500 nm.
3. The preparation method according to claim 1, characterized in that: (1) The molar ratio of aluminum oxide to silicon dioxide is 1:0.05-3, and the mass of iron oxide is 0.5-50% of the total mass of aluminum oxide and silicon dioxide.
4. The preparation method according to claim 1, characterized in that: (1) The ball milling time is 0.5 to 24 hours.
5. The preparation method according to claim 1, characterized in that: (2) The binder is a mixture of one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, methyl cellulose and polyvinyl alcohol; the added mass of the binder is 0.5 to 50% of the total mass of alumina, silica and silicon oxide.
6. The preparation method according to claim 1, characterized in that: (2) The medium pore-forming agent is a mixture of one or more of corn starch, nanocarbon, yellow dextrin, cyclodextrin, calcium carbonate, and melamine; the added mass of the pore-forming agent is 0.5 to 50% of the total mass of alumina, silica, and silicon oxide.
7. The preparation method according to claim 1, characterized in that: (3) The thickness of the green body is 0.5 to 2.5 mm.
8. The preparation method according to claim 1, characterized in that: (4) The sintering conditions are as follows: the temperature is raised from room temperature to 500°C at a rate of 0.5-10°C / min, then raised to 800°C at a rate of 0.5-15°C / min, kept at that temperature for 0.5-5h, and finally raised to 900-1600°C at a rate of 0.5-15°C / min, kept at that temperature for 0.5-12h, and then lowered to room temperature at a rate of 2-10°C / min.
9. An alumina-based catalytic ceramic membrane loaded with a high content of iron oxide prepared by the method according to any one of claims 1 to 8.
10. An application of the alumina-based catalytic ceramic membrane loaded with high iron oxide content as claimed in claim 9, characterized in that: Used for catalytic ozone oxidation to remove organic pollutants in water.
Citation Information
Patent Citations
Microfiltration ceramic membrane and production method thereof
CN108479420A
Microfiltration ceramic membrane and preparation method thereof
CN108585883A
Anti-pollution ceramic membrane as well as preparation method and application thereof
CN113926321A
Method for producing ceramic film and structure including ceramic film
JP2006188046A
Cited By
Method for high-temperature solid-phase synthesis of spessartite ceramic membrane with catalytic function and application of spessartite ceramic membrane
CN120550632A
Method for high-temperature solid-phase synthesis of manganese-aluminum garnet ceramic membrane with catalytic function and application
CN120550632B
Preparation method of metal-based ceramic composite membrane with ozone catalysis function
CN121623584A